Is it Possible to Avoid Sentinel Lymph Node Biopsy in Breast Cancer Patients with a Positive Axillary Lymph Node with Complete Pathological Response to Neoadjuvant Chemotherapy? - Souza, Helano de Paula Gonçalves (2023)
Introduction: Breast cancer represents 24.5% of new cases of cancer in women worldwide. Neoadjuvant chemotherapy is an important tool in the treatment of this pathology, allowing less aggressive surgeries at the breast and axilla, minimizing sequelae. Objective: Analyze the possibility of avoiding sentinel lymph node biopsy in patients with breast cancer who have undergone neoadjuvant chemotherapy and who present complete pathological response at the primary tumor and axilla, treated at a reference institution in Brazil’s Northeast. Method: Prospective, observational, cohort study in patients with breast cancer, undergoing neoadjuvant chemotherapy and operated at the Hospital Haroldo Juaçaba, from March 2019 to July 2021. Results: Forty-five female patients were enrolled in the study, with a mean age of 52.6 years. After neoadjuvant chemotherapy, nine patients (21.4%) had complete pathologic response at the breast and 17 (40.5%), complete pathologic response at the lymph nodes. Patients with complete response at the breast had a prevalence of complete response at lymph node 20.44 times higher than patients who did not have the same response. Conclusion: The complete pathologic response to neoadjuvant chemotherapy at the breast shows a tendency to predict the pathologic response at the axillary lymph nodes, reinforcing that, with this condition, sentinel lymph node biopsy could be avoided without causing harm to the local control of breast cancer.